PEMANFAATAN MEDIA INTERAKTIF WORDWALL DALAM MENINGKATKAN MOTIVASI BELAJAR BAHASA ARAB SISWA MAAHAD TAHFIZ AS-SAIDIYAH SEREMBAN, MALAYSIA - uin-malang-sitinahdiah siti halimah; Ainun Adib Rif'an Asshidiqi ABD MUID (FASAHAH, 2026)
Low motivation in learning Arabic among students of tahfiz institutions is a serious yet often overlooked challenge, primarily due to the intensive Al-Qur'an memorization program that exhausts students' cognitive energy before Arabic classes begin. This study aims to describe and analyze the improvement of students' Arabic learning motivation through the use of Wordwall interactive media at Maahad Tahfiz As-Saidiyah Seremban, Malaysia. This research employs a qualitative approach with a case study design, with Arabic students and teachers as research subjects. Data were collected through participatory observation, in-depth interviews, focus group discussions, and documentation, then analyzed using the interactive model by Miles, Huberman, and Saldana through the stages of data condensation, data display, and conclusion drawing. The findings reveal that Wordwall successfully increased students' active participation from 15-30 percent to 80 percent, transformed students' perception of Arabic from a burdensome subject into an anticipated learning experience, and fostered students' intrinsic motivation to master Arabic in a sustained manner. This study affirms that gamification-based interactive media can operate in harmony with religious educational traditions in tahfiz environments.